PENINGKATAN PENGETAHUAN IBU BALITA MELALUI PENGENALAN PROGRAM KADARZI DI KELURAHAN WONOKUSUMO SURABAYA[Increasing Mother Knowledge Through KADARZI Program in Wonokusumo Surabaya] - Riris Diana Rachmayanti (Media Gizi Indonesia, 2018)
The implementation of the KADARZI program has not been maximized due to the many families who do not know and do not understand the existence of the program. One area with low knowledge about the KADARZI program is the Wonokusumo Surabaya district. The purpose of this study was to analyze the improvement of mother knowledge after given an intervention in the Wonokusumo Sub-district of Surabaya and to identify factors that causing nutrition problems of children under fi ve (predisposing, reinforcing and enabling). This was a pre-experimental study with one group pretest-posttest design. The study was conducted in RW 02 Wonokusumo Village, January-February 2017. Data collection was carried out quantitative and qualitatively. A total of 38 mothers had children under fi ve and present at the posyandu in RW 2 were sampled in this study. Mother knowledge before and after the intervention were collected qualitatively. Paired sample t-test was used to analyze the differences. The qualitative data were collected through observation and in-depth interview to the head of RW 1 person and cadre (8 people). Interventions of health education using leafl et, video and simulation of making modisco (as one way to create and process nutritious local food). Intervention was conducted one time during the Posyandu. Activities were held once with 4 hours duration. The results showed that the knowledge score was increased from 47.9 to 82.6 there was a signifi cant increase in knowledge between before and after the intervention (p=0.043). The causes of nutritional problems in children under fi ve were 3 factors: predisposing, reinforcing, enabling. Health education interventions can improve maternal knowledge about the nutritional fulfi llment of children under five and the KADARZI program